The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acsbiomaterials.6b00030
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystalline Ordered Collagen Substrates for Applications in Tissue Engineering

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Incubation of acidic collagen solution in ammonia vapors induces a raise in pH without diluting the sample. The formation of collagen materials with a liquid crystalline order is not discussed in detail in this article, but they deserve special attention because they mimic collagen connective tissue organisations [ [80] , [81] , [82] , [83] ].…”
Section: Formation Of Native Collagen Fibrils In Vitro ...mentioning
confidence: 99%
“…Incubation of acidic collagen solution in ammonia vapors induces a raise in pH without diluting the sample. The formation of collagen materials with a liquid crystalline order is not discussed in detail in this article, but they deserve special attention because they mimic collagen connective tissue organisations [ [80] , [81] , [82] , [83] ].…”
Section: Formation Of Native Collagen Fibrils In Vitro ...mentioning
confidence: 99%
“…When the cells were seeded in a 3D hydrogel composed of the aligned nanofibrils, enhanced cellular outgrowth was induced via augmented expression of integrin α1, which resulted in arteriogenesis and blood perfusion recovery in the mouse ischemia model. In another study, hydrogel films made of concentrated collagen type I showed regular local alignments, which resulted in directed and oriented growth of human mesenchymal stem cells and their osteogenic differentiation [ 105 ]. Additionally, biomineralization-mimicking hybrid materials, using chitin nanowhisker gel matrices in a nematic phase as templates for CaCO 3 crystallization, have been reported [ 106 ].…”
Section: Reviewmentioning
confidence: 99%
“…Studies have shown that natural bone collagen exhibits a cholesteric lyotropic LC phase and an anisotropic surface, which can affect the contact guidance of cells, regulate the deposition of inorganic mineral salts, promote mineralization, and further promote bone tissue repair . Inspired by the LC properties of natural bone collagen, a collagen membrane with LC properties was prepared in vitro by neutralizing and fixing a highly concentrated acidic collagen solution with ammonia vapor; , however, its application is limited by poor mechanical strength and the tedious extraction process of raw materials.…”
Section: Introductionmentioning
confidence: 99%